Determinants of the Decision to Purchase Halal Toiletries with Trust as a Mediating Variable and Religiosity as a Moderation Among the Muslim Community in Padang City - Wahyu Sriutami; Hulwati; Aidil Novia (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
Halal Toiletries are personal care products produced in accordance with halal principles and are intended to meet the needs of Muslim consumers. The purpose of this study is to reveal the determinants of purchasing decisions for halal toiletries products, including halal awareness, brand image, and product quality with trust as a mediating variable and religiosity as a moderating variable. The method in this study uses quantitative, with the population being the Muslim community in Padang City who have purchased halal toiletries products. The sample size used 156 samples. The sampling technique used purposive sampling and technical analysis used Sem-PLS with Smart-PLS 4 software. The results of this study indicate that product quality and brand image variables have a positive and significant effect on purchasing decisions for halal toiletries products, while halal awareness has a negative and insignificant effect. Halal awareness and product quality have a positive and significant effect on purchasing decisions for halal toiletries products with trust as a mediator, while brand image has a positive and insignificant effect on purchasing decisions with trust as a mediator. Halal awareness has a positive and insignificant effect on purchasing decisions for halal toiletries products with religiosity as a moderating factor. Product quality has a negative and insignificant effect on purchasing decisions for halal toiletries, with religiosity as a moderating factor. Therefore, this study offers insights for the halal industry in optimizing product quality and brand image to influence consumer purchasing decisions for halal products